Recent advances in the message passing interface 19th European MPI Users' Group Meeting, EuroMPI 2012, Vienna, Austria, September 23-26, 2012. Proceedings - Benkner, Siegfried; Dongarra, Jack J.; Traff, Jesper Larsson (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 19th European MPI Users' Group Meeting, EuroMPI 2012, Vienna, Austria, September 23-26, 2012. The 29 revised papers presented together with 4 invited talks and 7 poster papers were carefully reviewed and selected from 47 submissions. The papers are organized in topical sections on MPI implementation techniques and issues; benchmarking and performance analysis; programming models and new architectures; run-time support; fault-tolerance; message-passing algorithms; message-passing applications; IMUDI, improving MPI user and developer interaction.